Performance Enhancement of Wireless Sensor Network with Adaptive Modulation Scheme - Rathod, Chetan; Sharma, Rahul (International Journal of Computer Sciences and Engineering, 2015)
The wireless sensor network refers to a group of spatially distributed and dedicated sensors for monitoring and recording the physical conditions of environment like temperature, humidity, pollution levels, sound, wind speed with direction and pressure. The sensors are self powered nodes which also possess limited processing capabilities and the nodes communicate wirelessly through a gateway. Simulation results based upon this protocol identify some important factors that induce unbalanced energy consumption among sensor nodes and hence affect the lifetime network. This highlights the need for an adaptive clustering protocol that can increase the network lifetime by further balancing the energy consumption among sensor nodes.